Percutaneous thoracostomy with thoracic lavage for traumatic hemothorax: a performance improvement initiative - Michael A Vella; Ryan Peter Dumas; Jeremy W Cannon; Ali Ali; Jay Yelon; Carl A Beyer; Martha M Brinson; Nathaniel McLauchlan; Sarah M Joergensen (Trauma Surgery & Acute Care Open)
Objectives Percutaneously placed small-bore (14 Fr) catheters and pleural lavage have emerged independently as innovative approaches to hemothorax management. This report describes techniques for combining percutaneous thoracostomy with pleural lavage and presents results from a performance improvement series of patients managed with percutaneous thoracostomy with immediate lavage.Methods This was a prospective performance improvement series of patients treated at a level 1 trauma center with percutaneous thoracostomy and immediate lavage between April 2021 and May 2023.Results Percutaneous thoracostomy with immediate lavage was used to treat nine hemodynamically normal patients with acute hemothorax. Injuries included both blunt and penetrating mechanisms. 56% of patients presented immediately after injury, and 44% presented in a delayed fashion ranging from 2 to 26 days after injury. Median length of stay was 6 days (IQR 6, 9). Seven patients were discharged home in stable condition, one was discharged to an acute rehabilitation facility, and one was discharged to a skilled nursing facility.Conclusions Percutaneous thoracostomy with pleural lavage is clinically feasible and effective and warrants further evaluation with a multicenter clinical trial.Level of evidence Therapeutic/care management, level V.